The effects of cardiovascular disease on the clinical outcome of elderly patients with diffuse large B-cell lymphoma. Issue 3 (March 2015) - Tsai, Huei-Ting; Pfeiffer, Ruth M.; Warren, Joan; Wilson, Wyndham; Landgren, Ola
Abstract: We identified 3910 elderly (>65 yrs) patients with diffuse large B-cell lymphoma (DLBCL) who received doxorubicin-based (+/−rituximab) therapy and 77 347 cancer-free controls, and assessed cardiovascular events and survival in relation to preexisting cardiovascular comorbidities. Compared to controls, patients with DLBCL had a 3.4-fold (95%CI 3.0–3.9) and 2.5-fold (95%CI 2.3–2.7) increased risk of congestive heart failure (CHF)/cardiomyopathy (CM) within 6 months and 3 years of diagnosis, respectively. Risk of acute myocardial infarction (AMI) was similarly increased. The risk of CHF/CM and AMI was significantly higher in those patients with DLBCL (vs. controls) who did not report preexisting cardiovascular disease, compared to those who had preexisting cardiovascular disease; this was due to dose reductions of doxorubicin among patients with preexisting cardiovascular disease. Rituximab improved survival in patients with stage III–IV (but not I–II) disease (p-interaction = 0.0003). Our novel findings emphasize the need to reduce cardiac toxicity of doxorubicin in elderly DLBCL patients.